Voltammetric studies of the reactions of iron-sulphur clusters ([3Fe-4S] or [M3Fe-4S]) formed in Pyrococcus furiosus ferredoxin. - Fawcett, SE; Davis, D; Breton, J; Thomson, A; Armstrong, F (1998)
Reactions of the [3Fe-4S] cluster and various metallated [M3Fe-4S] adducts co-ordinated in the ferredoxin from the hyperthermophile Pyrococcus furiosus have been studied by protein-film voltammetry, bulk-solution voltammetry, solution kinetics and magnetic CD (MCD). The [3Fe-4S] cluster exhibits two couples, [3Fe-4S]+/0 and [3Fe-4S]0/2-. Film voltammetry is possible over a wide pH range (2-8), revealing that the [3Fe-4S]+/0 couple shows a complex pH dependence with pKred1=2.8, pKox=4.9 and pKred2=6.7. From MCD, pKred1 corresponds with protonation of [3Fe-4S]0 to give a spectroscopically distinct species, as reported for ferredoxins from Azotobacter and Sulfolobus. The status of the disulphide/disulphydryl entity makes no significant difference to the data (given for the -S-S- form). Formation of the hyper-reduced [3Fe-4S]2- state is observed, requiring 3H+ for the overall 3e- reduction of [3Fe-4S]+, the change therefore being electroneutral. By comparison with the ferredoxin from Desulfovibrio africanus, uptake of Fe(II) and other M(II) by [3Fe-4S]0 to give [M3Fe-4S] clusters is slow (t1/2>10 min at room temperature, slower still if the protein is adsorbed on the electrode), whereas reaction with Tl(I) to produce [Tl3Fe-4S] is very rapid (t1/2<<1 s), suggesting that co-ordination of Tl does not require reorganization of the protein structure. Rates of formation of [3Fe-4S] from [M3Fe-4S] adducts increase sharply at high potentials, showing that metal release involves a labile 'super-oxidized' [M3Fe-4S]3+ state.